Brazil : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper examines the proximate causes of dramatic fall in investment in Brazil and the prospects for investment going forward. A variety of factors contributed to the investment decline, including deterioration in Brazil's medium-term growth prospects, rising real interest rates, falling terms of trade, rising uncertainty related to economic policy, rising levels of corporate leverage and lower cash flow. Some of the factors that have weighed on investment over recent years have begun to normalize providing some impetus for a recovery. However, still-high levels of corporate leverage and the prospect of continued uncertainty related to economic policy settings suggest a turnaround in investment is likely to be subdued.